Human resource management in emerging economies - Zientara, Piotr (Routledge studies in employment and work relations in context, 2014)
The demise of communism in 1989 in eastern Europe, followed by the break-up of the Soviet Union and the spectacular rise of China and India in the 1990s, brought about a new world order. In eastern Europe communism not only caused large-scale impoverishment and technological slowing, but also signified managerial wastefulness and disregard for employee voice